The determinants of auditor switching: The role of audit committee, firm size, audit fees, and financial distress with audit quality as a moderator - Dinda Oktavia; Harry Budiantoro; Hestin Agus Tantri Ningsih (LPMP Imperium, 2026)
This study aims to analyze the factors influencing auditor switching, considering audit quality as a moderating variable. The phenomenon of auditor switching in Indonesia is becoming increasingly relevant with the introduction of auditor rotation regulations and the growing demand for good corporate governance. This study uses secondary data in the form of audited financial statements of companies included in the Sri Kehati index for the 2019–2023 period. Data analysis was conducted using SPSS 31 to examine the effects of the audit committee, company size, audit fees, and financial distress on auditor switching, with audit quality as a moderating variable. The results show that the audit committee does not affect auditor switching, whereas company size, audit fees, and financial distress do. Furthermore, audit quality is unable to moderate the influence of the four independent variables on auditor switching. These findings conclude that the decision to switch auditors is more determined by internal company factors, particularly financial condition and audit fees, than by the audit committee's role or audit quality. Public interest statements The managerial implications of this study emphasize the need for company management to carefully consider factors such as cost, independence, and financial condition before making auditor-switching decisions, and for regulators to ensure that auditor-switching practices are carried out in accordance with the principles of transparency and good governance.